Characterization of the behavioural phenotype of calpain-knockout mice - Silva, Joana Andreia Joaquim da (2016)
Adult neurogenesis consists of the production of new neurons in specific brain regions, or neurogenic niches. The most relevant niches in rodents are the subventricular zone lining the lateral ventricles and the dentate gyrus of the hippocampus. Neurogenesis has been shown to influence cognitive function dependent on these regions. Evidence from the literature suggests that calpains are able to influence neurogenesis. However, little information is available regarding their participation in neurological functions. We have evaluated the involvement of calpains in cognitive and emotional behaviour by evaluating these functions in mice genetically modified to lack calpain 1, calpain 2, or both calpains. In this work, 12 week old calpain knockout mice for calpain 1, calpain 2, both, or wild type (WT) littermates were used. The mice were tested in the open field, object recognition, Morris water maze, contextual and cued fear conditioning, passive avoidance, elevated plus maze and forced swimming tests, to evaluate neurological function. Results from the elevated plus maze show that calpain2 knockout mice and double knockout mice present an anxious phenotype comparing with WT mice, suggesting that calpain 2, but not calpain 1, is involved in anxiety. Memory, learning, locomotor activity and exploratory behaviour as well as helplessness were similar in calpain knockout and WT mice. Neurogenesis in calpain knockout mice was also similar to WT mice. Overall, our work shows that calpain 2 is involved in anxiety and a clear phenotype was identified in calpain knockout mice regarding their involvement in memory and learning, which is agreement with previously published data using mice that lack the small regulatory subunit of calpains.